Production processes of media discourse-sport: watching the news coverage of the Games Open Santa Catarina - 2007 - Bitencourt, Fernando Gonçalves (2009)
This study aimed to understand the processes and conditions of news production, having the cover of the final round of the 47 º Open Games of Santa Catarina (JASC) as the object of study, held in Florianopolis, 2007. We made one participant observation and had a dialogue with professionals from television, radio and newspaper. We registered information in field diaries and photographs, describing and interpreting the spatial structure, the system of objects and the actions of journalists in their practice. It was possible to discover that the production of sports news is revealed as a power to make see (and believe) while presenting some structural constraints (economic, organizational, cultural) that restrict the journalistic work, and make difficult the systematic reflection about the carrying out of such work.